Precedent and development of law: Is it time for greater transparency in International Commercial Arbitration?. (5th April 2018) - Pislevik, Stefan
Abstract: International Commercial Arbitration (ICA) continues to be widely chosen as the preferred method of dispute resolution for parties, particularly where matters cross international boundaries. However, with the divergence of cases from open courts to predominantly closed arbitration hearings, questions of transparency have, and will continue to arise. This article is situated within the framework of transparency and asks whether confidentiality should still hold to be the norm in arbitration. Additionally, questions are asked around the development of law and operation of precedent in ICA. Indeed, what this article ultimately seeks to achieve is evaluating whether arbitration can serve as a mechanism for generating privately made law.